Polímeros biodegradables a base de almidón y compuestos biodegradables - Cyras, Viviana Paola (2005)
Biodegradable plastics are a new generation of materials, still at an early stage of development is tied to the growth of composting infrastructures, to the definition of severe standards for biodegradability and compostability, and to the marketing of effective and truly compostable products.  Among the biodegradable synthetic polymers that have been developed so far, poly-hydroxy butyrate-valerate (Zeneca), poly-lactides (Cargill), poly-caprolactone (Unión Carbide), cellulose acetate (Eastman Chemical), poly-aspartic acid (Rohm and Haas), MaterBiZ, blends with starch and poly-caprolactone (Novamont). Starch is an abundant, inexpensive, natural raw material. Starch is totally biodegradable in a wide variety of environments and could permit the development of totally degradable products for specific market demands. This review presents the reported work on type, properties and use of biodegradable polymers.